2018
DOI: 10.1177/0265407518769387
|View full text |Cite
|
Sign up to set email alerts
|

Smartphones distract parents from cultivating feelings of connection when spending time with their children

Abstract: In the U.S., 95% of smartphone users admit to having used their smartphones during their latest social gathering. Although smartphones are designed to connect us with others, such smartphone use may create a source of distraction that disconnects us from the people in our immediate social environment. Focusing on one fundamental social relationship-between parents and their children-we examined whether smartphones made parents feel distracted, thereby undermining key benefits parents reap when spending time wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 41 publications
0
91
1
6
Order By: Relevance
“…49 It is also worth reminding parents that they model smartphone use with their own behaviour; a randomized study showed that heavy parental smartphone use was associated with poorer quality of interactions with their children. 50 Youth and their families can be encouraged to set boundaries for smartphone and social media use. These could include such measures as using social media only for set times, and preferably only in common living areas in the home.…”
Section: How Might Physicians Use This Evidence To Inform Their Practmentioning
confidence: 99%
“…49 It is also worth reminding parents that they model smartphone use with their own behaviour; a randomized study showed that heavy parental smartphone use was associated with poorer quality of interactions with their children. 50 Youth and their families can be encouraged to set boundaries for smartphone and social media use. These could include such measures as using social media only for set times, and preferably only in common living areas in the home.…”
Section: How Might Physicians Use This Evidence To Inform Their Practmentioning
confidence: 99%
“…Experimental work also corroborates these anecdotes. Kushlev and Dunn () assigned parents spending time with their children at a museum to either frequently use their phones or infrequently use their phones. Afterward, parents in the frequent phone use group felt more distracted and experienced less connection and sense of meaning out of their time spent with their children.…”
Section: How Does This Use Impact Parents and Parenting?mentioning
confidence: 99%
“…Furthermore, observations have been done at restaurants, playgrounds, doctor offices, and in the lab, and all of these observational studies suggest very similar conclusions—i.e., parent phone use is associated with less verbal interaction, lower parental responsiveness, and at times harsher parental responses (Abels et al, ; Davidovitch et al, ; Hiniker et al, ; Kellershohn, Walley, West, & Vriesekoop, ; Radesky et al, ; Radesky et al, ; Reed, Hirsh‐Pasek, & Golinkoff, ). Parental daily survey reports also suggest parents feel less connected to their children when their time together involved parent phone use (Kushlev & Dunn, ). Additionally, in parent‐report data, an association has been found between greater parent difficulties with managing their phone use while with their children and worse overall parenting quality—i.e., greater parenting laxness and overreactivity (McDaniel, Everest, & White, ).…”
Section: How Does This Use Impact Parents and Parenting?mentioning
confidence: 99%
“…To highlight one example, parents who were assigned to use their smartphones frequently (versus infrequently) while with their children reported feeling less attentive and consequently less socially connected to them [43]. As another example, individuals assigned to navigate to a new location using their smartphone (versus no phone) were able to find the location more easily but also felt less socially connected [42 ].…”
Section: Disruptionmentioning
confidence: 99%